Coexistence mechanisms and individual trophic niche variation between functionally analogous non-native and native carp species - Yingqiu Zhang; J. Robert Britton; Daotian Huang; Yujie He; Yuefei Li; Weitao Chen; Jie Li (Scientific Reports)
Abstract Understanding the mechanisms that promote coexistence between functionally analogous non-native and native species that share similar prey is important for predicting the ecological consequences of their competitive interactions. Theory predicts that species coexistence is facilitated by stabilizing mechanisms that enhance inter-specific trophic niche partitioning, and/ or the equalizing mechanisms that reduce differences in the average fitness. Inter-specific niche partitioning, influenced by the ecological opportunity in prey resources, also affects intra-specific niche partitioning and individual niche expansion. These theories were tested using the non-native mrigal carp Cirrhinus mrigala and its congener native mud carp C. molitorella that coexist across the Pearl River basin, Southern China, with their trophic interactions analysed using DNA metabarcoding on fish gut contents sampled across the basin in both the dry and wet seasons of 2019 and 2021. The results revealed that the inter-specific trophic niche overlap was lower than their intra-specific trophic niche overlap, suggesting their coexistence was supported by stabilizing mechanisms. The ecological opportunity in prey resources was driving inter-specific niche partitioning and this partitioning then positively influenced intra-specific niche partitioning and individual niche expansion, especially in mrigal carp that had larger body sizes and occupied higher trophic positions at constricted individual niches. Fish body size also affected inter-specific niche partitioning and the relationship between inter- and intra-specific niche partitioning, with positive effects on both in mrigal carp but negative effects on both in mud carp. The results thus provide a mechanistic explanation on how closely related non-native and native species coexist and highlight the importance of dietary plasticity in facilitating the invasion of non-native species.